Insting Bunda (Instant Nesting Bed) untuk Meningkatkan Kualitas Tidur Bayi: Insting Bunda (Instant Nesting Bed) to Improve Baby's Sleep Quality - Eldin Yafi Fahmika; Happy Dwi Aprilina (Universitas Ngudi waluyo, 2025)
The quality of a baby's sleep is a very important factor in supporting their development and growth. When sleeping, a baby's body produces three times more growth hormones than when they are awake. Babies need around 15-17 hours of sleep per day, divided into 8 hours of daytime sleep and 9 hours of nighttime sleep. If this amount of sleep is not fulfilled, it will have a negative impact on the baby's physiological and psychological balance. One way to improve a baby's sleep quality is by using a nesting bed. However, problems often arise when using nesting beds for babies. Innovation is needed to maximize the function of nesting beds. The purpose of this study is to test an innovative nesting bed to improve sleep quality in babies, named “Insting Bunda : Instant Nesting Bed to Improve Baby Sleep Quality.” The research method used was quantitative with a pre-experimental research design and a pretest-posttest one-group design conducted at the Sokaraja 1 Community Health Center, Sokaraja District, Banyumas Regency. The subjects of this study were 10 infants aged 1-12 months. The results of this study showed that after the provision of the Instant Nesting Bed Insting Bunda innovation tool, 9 out of 10 infants experienced an improvement in sleep quality in the good category with an average of 97.5%. Before the provision of the tool, the sleep quality of all respondents was in the poor category with an average of 32.5%. Based on the Wilcoxon analysis test, the results showed a ρ value of 0.004 < 0.05, indicating that the Instant Nesting Bed Insting Bunda innovation tool has a significant effect on improving infant sleep quality. The Instant Nesting Bed Insting Bunda innovation tool is highly recommended for use with infants to help improve their sleep quality. Abstrak Kualitas tidur bayi merupakan faktor yang sangat penting untuk menunjang perkembangan dan pertumbuhannya. Saat tidur, tubuh bayi memproduksi hormon pertumbuhan tiga kali lebih banyak dibandingkan ketika bayi terbangun. Bayi membutuhkan durasi tidur sekitar 15-17 jam perharinya dengan pembagian waktu 8 jam untuk tidur siang dan 9 jam untuk tidur malam. Apabila durasi tidur tidak terpenuhi, maka akan berakibat buruk pada keseimbangan fisiologi dan psikologis bayi. Salah satu cara untuk meningkatkan kualitas tidur bayi adalah dengan menggunakan nesting. Seringkali terjadi permasalahan dalam penggunaan nesting pada bayi. Diperlukan inovasi untuk memaksimalkan fungsi nesting. Tujuan dari penelitian ini adalah menguji alat inovasi nesting untuk meningkatkan kualitas tidur pada bayi yang diberi nama ‘’Insting Bunda (Instant Nesting Bed) Untuk Meningkatkan Kualitas Tidur Bayi’’. Metode penelitian ini adalah metode kuantitatif dengan desain penelitian pre-eksperimental dan rancangan Pretest – Postest One Group Desain yang dilakukan di Puskesmas Sokaraja 1, Kecamatan Sokaraja, Kabupaten Banyumas. Subjek penelitian ini adalah bayi berusia 1-12 bulan dengan jumlah 10 bayi. Hasil penelitian ini adalah setelah pemberian Insting Bunda (Instant Nesting Bed), 9 dari 10 bayi mengalami peningkatan kualitas tidur pada kategori baik dengan rata-rata 97,5 %. Sebelum pemberian alat, kualitas tidur seluruh responden berada dalam kategori kurang dengan rata-rata 32,5 %. Berdasarkan uji analisis Wilcoxon menunjukkan hasil ρ value 0,004 < 0,05 artinya menunjukkan bahwa Insting Bunda (Instant Nesting Bed) memiliki pengaruh signifikan terhadap peningkatan kualitas tidur bayi. Alat inovasi Instant Nesting Bed Insting Bunda sangat layak digunakan pada bayi guna membantu meningkatkan kualitas tidur bayi.